Ebola response in Sierra Leone: The impact on children. (5th July 2016) - Fitzgerald, Felicity; Awonuga, Waheed; Shah, Tejshri; Youkee, Daniel
Summary: The West African Ebola virus disease (EVD) outbreak is the largest ever seen, with over 28, 000 cases and 11, 300 deaths since early 2014. The magnitude of the outbreak has tested fragile governmental health systems and non-governmental organizations (NGOs) to their limit. Here we discuss the outbreak in the Western Area of Sierra Leone, the shape of the local response and the impact the response had on caring for children suspected of having contracted EVD. Challenges encountered in providing clinical care to children whilst working in the "Red Zone" where risk of EVD is considered to be highest, wearing full personal protective equipment are detailed. Suggestions and recommendations both for further research and for operational improvement in the future are made, with particular reference as to how a response could be more child-focused.